Alkaline Dehydration of Human Urine Collected in Source-Separated Sanitation Systems Using Magnesium Oxide - Simha, Prithvi; Friedrich, Christopher; Randall, Dyllon Garth; Vinnerås, Björn (Frontiers in Environmental Science, 2021)
Fresh human urine, after it is alkalised to prevent the enzymatic hydrolysis of urea, can be dehydrated to reduce its volume and to produce a solid fertiliser. In this study, we investigated the suitability of MgO to alkalise and dehydrate urine. We selected MgO due to its low solubility (<2 g L-1) and relatively high saturation pH (9.9±0.2) in urine. Using a laboratory-scale setup, we dehydrated urine added to pure MgO and MgO mixed with co-substrates (biochar, wheat bran, or calcium hydroxide) at a temperature of 50 °C. We found that, dehydrating urine added to a mixture of MgO (25% w/w), biochar, and wheat bran resulted in a mass reduction of >90% and N recovery of 80%, and yielded products with high concentrations of macronutrients (7.8% N, 0.7% P and 3.9% K). By modelling the chemical speciation in urine, we also showed that ammonia stripping rather than urea hydrolysis limited the N recovery, since the urine used in our study was partially hydrolysed. To maximise the recovery of N during alkaline urine dehydration using MgO, we recommend treating fresh/un-hydrolysed urine a temperature <40 °C, tailoring the drying media to capture NH_4^+ as struvite, and using co-substrates to limit the molecular diffusion of ammonia. Treating fresh urine by alkaline dehydration requires only 3.6 kg MgO cap-1y-1 and a cost of US$ 1.1 cap-1y-1. Therefore, the use of sparingly soluble alkaline compounds like MgO in urine-diverting sanitation systems holds much promise.